2020
DOI: 10.1016/j.nicl.2020.102481
|View full text |Cite
|
Sign up to set email alerts
|

CSF dynamics disorders: Association of brain MRI and nuclear medicine cisternogram findings

Abstract: Highlights MR features of DESH are associated with abnormalities on NM cisternogram. These finding support DESH as an indicator of a CSF dynamics disorder. Abnormal radiotracer distribution is more frequent in DESH vs ventriculomegaly or high convexity tight sulci alone. Abnormal radiotracer distribution is more frequent with ventriculomegaly or HCTS vs neither. These findings indicate that CSF dynamics disorders occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Reflux grades 3 to 4 were observed in 46/92 patients (50%), characterized by a high degree of tracer enrichment in lateral ventricles at 24 h. If the CSF of the ventricles is replaced by CSF reproduction three times over 24 h, the continued presence of tracer at 24 h suggests either reduced formation of CSF or increased dispersion. A recent nuclear medicine cisternogram study found the radiotracer to more frequently enrich in lateral ventricles, though being absent or delayed over cerebral convexity, of individuals with DESH sign and high convexity tight sulci [ 38 ]. The latter is seen in iNPH patients (see Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Reflux grades 3 to 4 were observed in 46/92 patients (50%), characterized by a high degree of tracer enrichment in lateral ventricles at 24 h. If the CSF of the ventricles is replaced by CSF reproduction three times over 24 h, the continued presence of tracer at 24 h suggests either reduced formation of CSF or increased dispersion. A recent nuclear medicine cisternogram study found the radiotracer to more frequently enrich in lateral ventricles, though being absent or delayed over cerebral convexity, of individuals with DESH sign and high convexity tight sulci [ 38 ]. The latter is seen in iNPH patients (see Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic positron emission tomography (PET) with radionuclide injected intravenously or intrathecally has also been used to investigate the main clearance and drainage pathways of PVS fluid ( Cogswell et al, 2020 ; de Leon et al, 2017 ), although the limited anatomic resolution of PET scans does not currently enable the visualization of the details of the perivascular system.…”
Section: Imaging Pvs Functionmentioning
confidence: 99%
“…This “disproportionately enlarged subarachnoid-space hydrocephalus” (DESH) ( 43 , 44 ) is found in many but not all ( 45 ) cases of iNPH, and as a potential marker of response to shunt surgery ( 44 , 46 , 47 ), some centres have incorporated it into management pathways ( 30 ). The pathophysiological mechanisms underlying DESH are unclear but it is likely to be associated with disrupted CSF dynamics ( 48 ).…”
Section: Imagingmentioning
confidence: 99%
“…A number of recent studies have now investigated the presence of DESH in the wider population, where it is found in 1–7% and associated with poorer cognition ( 49 52 ). A study examining over a thousand participants with either no or only mild cognitive impairment found that DESH was a predictor of progressive cognitive decline independent of established features including age, cortical thickness, or APOE status ( 48 ). There is also evidence that in some cases DESH may be a marker of preclinical iNPH: a long term follow up study of asymptomatic individuals with DESH imaging features found that approximately 17% per year subsequently progressed to symptomatic iNPH ( 53 ).…”
Section: Imagingmentioning
confidence: 99%